THE APPLICATION OF THE PROBLEM BASED LEARNING MODEL TO IMPROVE THE CRITICAL THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTs - Ansya, Yusron Abda'u; Salsabilla, Tania (Universitas Negeri Medan, 2024)
The purpose of this study is to investigate how the Problem Based Learning paradigm can help primary school pupils develop their critical thinking abilities. Five class instructors and twenty fifth-grade students at SD Muhammadiyah 29 Sunggal Elementary School participated in interviews, observations, and documentation as part of the qualitative descriptive methodology utilised to collect data. As demonstrated by the research findings, the Problem Based Learning significantly improves students' critical thinking abilities and increases their level of active engagement, opinion courage, and enthusiasm for learning. Even if there are obstacles to its implementation, like instructors' ignorance and a lack of resources, this study suggests that teachers should receive training and support from parents and associated organisations. It is anticipated that this study will give participants in initiatives to raise the standard of education in Indonesia fresh perspectives.